Pharmaceutical care in Alzheimer's disease - Vezmar Kovačević, Sandra (Archives of Pharmacy, 2020)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive memory and cognitive function impairment as well as behavioural and psychiatric disturbances. Pharmaceutical care involves the process of identifying, resolving, and preventing drug-related problems, and it is aimed at improving the patient’s quality of life. AD is usually diagnosed in elderly patients with comorbidities and, consequently, a variety of drug-related problems may occur. Pharmacists should focus on adverse reactions, drug-drug interactions, and adherence in patients with AD. The introduction of acetylcholinesterase inhibitors in treatment may be associated with adverse effects, such as diarrhoea, muscle cramps, fatigue, nausea, vomiting, insomnia, anorexia, headache, and dizziness, which may be transient or require an alternative medication. Use of anticholinergic medications, bradycardia causing medications, antipsychotics and other medications should be assessed carefully because of potential drug-drug interactions with acetylcholinesterase inhibitors, especially rivastigmine. Adherence may be a major drug-related problem in patients with AD because of the nature of illness and appropriate communication between pharmacists and patients or carers requiring adequate skills and knowledge. Although AD is increasing in prevalence there is a lack of evidence about the impact of pharmaceutical care on the treatment outcomes and quality of life of patients and more research is needed in this area.
Keywords: Alzheimer's disease, pharmaceutical care, drug-drug interactions, adverse reactions, adherence